حركة الشبان و نشاطهم السياسي 1900-1919 - ابتسام مراح; د/ عبدالرحمان قفاف (My University, 2024)
ملخص باللغة العربية: عاشت الجزائر خلال الفترة الاستعمار ظروفا قاسية ، مست جميع الميادين لاسيما منها الميدان الثقافي بحيث حاول المستعمر تهديم الهوية الجزائرية الأصيلة واستبدالها بالمدرسة الفرنسية لأنها تعد أساس كل تقدم في المجتمع ، و إذا كانت كذلك في الأمور العادية ، فهي عامل من عوامل التجهيل عندما تصبح إحدى أدوات العمل الاستعماري ، فالاستعمار الفرنسي في الجزائر تبلى سياسة تعليمية إزاء بعض الجزائريين ، لكن في إطارها التجهيلي، انطلاقا من محاربة اللغة العربية والدين الإسلامي ومحاولة فرض ونشر اللغة و الثقافة الفرنسية . وقد نتج عن هذه الوضعية ، ظهور حركة الشبان الجزائريين ، بشقيها الكتلة المحافظة والنخبة المفرنسة لسانا وفكرا ، وكلاهما تأثر بالظروف السائدة داخل و خارج الجزائر ، مما أدى إلى ظهور الحركة الوطنية التي اتخذت أشكالا مختلفة للوصول إلى غاية مشتركة ؛ وكانت نتيجة لجهود بعض العلماء في أواخر القرن 19 وبداية القرن 20 . Summary in Arabic: During the colonial period, Algeria lived through harsh conditions that affected all fields, especially the cultural field, so that the colonizer tried to destroy the authentic Algerian identity and replace it with the French school because it is the basis of all progress in society, and if it is like that in ordinary matters, it is a factor of ignorance when it becomes one of the tools. Colonial action. French colonialism in Algeria implemented an educational policy towards some Algerians, but within its ignorance framework, based on the fight against the Arabic language and the Islamic religion and the attempt to impose and spread the French language and culture. This situation resulted in the emergence of the Algerian youth movement, with its two parts, the conservative bloc and the French elite, both in language and thought, both of which were affected by the conditions prevailing inside and outside Algeria, which led to the emergence of the national movement that took different forms to reach a common goal. " It was the result of the efforts of some scientists in the late 19th century and the beginning of the 20th century.